Steady-state size distribution of air bubbles in polar ice - V. Ya. Lipenkov; A. N. Salamatin (Лëд и снег, 2015)
Between the close-off depth and the bubble-to-hydrate transition zone in polar ice sheets, the geometrical properties of air bubbles, such as number concentration and size of bubbles, are mainly controlled by firn temperature and ice accumulation rate prevailing during the snow to ice transformation [3], and by the bubble compression in the course of bubbly ice densification [13]. This implies that the data on the bubble properties can be used for reconstruction of the past climate change. On the basis of our earlier studies of bubbly ice densification and the new measurements of air bubbles in the Antarctic ice cores, we have developed a theory of bubble evolution in polar ice and propose an inverse procedure for bubble size conversion to specified conditions at the close-off depth. Both outcomes of the research contribute to elaboration of the new paleoclimatological tool based on the bubble properties.